Pengaruh Pertumbuhan Laba, Investment Opportunity Set dan Ukuran Perusahaan terhadap Kualitas Laba - Muhammad Yusuf; Dimas Wicaksono; Epy Nuryanti (AKRUAL : Jurnal Akuntansi dan Keuangan, 2021)
The purpose of this study was to obtain empirical evidence regarding the problem under study, namely "The Effect of Profit Growth, Investment Opportunity Set and Company Size on Earning Quality in Food and Beverage Sector Companies listed on the IDX for the 2016-2019 period". The number of companies that were sampled in this study were 12 companies. Determination of the sample in this study using purposive sampling technique. Testing the hypothesis in this study using the Panel Data analysis method using the E-VIEWS 10 program. The results showed that:(1) Profit Growth had no effect on Earnings Quality, (2) Investment Opportunity Set had no significant effect on Earnings Quality, (3) and Firm Size had no effect on Earnings Quality.